Safety assessment of equine allogeneic tenogenic primed mesenchymal stem cells in horses with naturally occurring tendon and ligament injuries - Carlier, Stephanie; Depuydt, Eva; Van Hecke, Lore; Martens, Ann; Saunders, Jimmy; Spaas, Jan H. (Frontiers in Veterinary Science, 2024)
Background Mesenchymal stem cells provide a valuable treatment option in orthopedic injuries in horses. Objectives The aim of this study was to evaluate the hematological, biochemical, immunological and immunomodulatory parameters following intralesional treatment with tenogenic primed equine allogeneic peripheral blood-derived mesenchymal stem cells (tpMSCs) in client-owned horses with naturally occurring superficial digital flexor tendon (SDFT) and suspensory ligament (SL) injuries. Methods The immunogenicity and immunomodulatory capacities of tpMSCs were assessed in a modified mixed lymphocyte reaction, including peripheral blood mononuclear cells (PBMCs) of 14 horses with SDFT and SL injuries after treatment with tpMSCs. In a second study, 18 horses with SDFT and SL injuries received either an intralesional injection with tpMSCs (n = 9) or no treatment (n = 9). Results The tpMSCs did not provoke a cellular immune response (p < 0.001) and were able to immunomodulate stimulated T lymphocytes (p < 0.001) in vitro. Therapeutic use of tpMSCs did not result in relevant hematologic or biochemical abnormalities. Main limitations Both studies had a small sample size. No statistical analyses were performed in the second study. Fibrinogen was only analyzed in a single horse prior to treatment. Conclusion Co-incubation of tpMSCs and PBMCs of horses that have been previously exposed to tpMSCs did not elicit a cellular immune response and tpMSCs were able to immunomodulate stimulated T lymphocytes. Intralesional treatment with tpMSCs did not provoke abnormal changes in hematological and biochemical parameters.